The importance of patient satisfaction and health-related quality of life after renal transplantation - (:unkn) unknown (ELSEVIER SCIENCE INC, 2006)
In the last decade, patient satisfaction and quality of life have been accepted as important components of quality of medical care. Therefore, the purpose of this study was to examine and compare the quality of life and satisfaction in renal transplant patients with end-stage renal disease. In this cross-sectional study, quality of life and patient satisfaction were analyzed in 356 renal transplant recipients, 104 hemodialysis patients, 186 peritoneal dialysis patients. All patient groups were asked to estimate their subjective quality of life and satisfaction by responding to Turkish adapted instruments PSQ III (patient satisfaction questionnaire), 15D (quality of life), and sociodemographic data. The patient satisfaction (PSQ III) and quality of life (15D) mean scores were apparently better among male renal transplant than peritoneal or hemodialysis patients (P <.05). Married transplant patients' health-related quality of life (F = 4.64; P <.05) and satisfaction (F = 4.57; P <.05) mean scores were significantly higher than single or widowed patients. Total scores on the PSQ III showed a significant positive correlation with the total scores of the 15D (r =.842; P <.0001). In this study, the benefits of kidney transplantation were documented by means of satisfaction and quality-of-life assessments. The Turkish adapted PSO III 18-item scale has excellent reliability and validity. The measure may be valuable for use in clinical trials or routine patient care.
Keywords: INSTRUMENT; TRANSLATION; EDUCATION; TURKEY